(untitled) (Journal of Geography and Environmental Management, 2020)
In this paper, were analyzed long-time course of atmospheric circulation forms, the main ice parameters, average air temperature and the sum of negative air temperatures. Database was formed by air temperature, ice thickness and types of circulation. For types of atmospheric circulation the long-term average was recalculated. Between parameters are revealed correlations. According researches results, ice thickness was decrease with different weight. In the Caspian Sea, a decrease in ice thickness is observed. The average ice thickness is 40 cm. In the Middle Caspian, an increase in the frequency of ice cover is observed. The estimated contribution of each month to the cold season. The temperature effect of each month of the cold period and each type of atmospheric circulation effect were estimated. In the time course a stepwise transition from one stationary state to another was determined. This was reflected not only on the temperature, but also on all the parameters considered. The classification of winter species of the Caspian Sea under consideration, according to which there is an increase in the frequency of occurrence of mild and moderate winters.